Determinasi Investasi Sektor Publik Bidang Pendidikan Dan Kesehatan Terhadap Tingkat Kesejahteraan Masyarakat Di Kabupaten Tulungagung - Tito Setiawan; Nafik Umurul Hadi (Mathematics Education Study Program, 2025)
The level of welfare is a very important thing considering that welfare is a measuring point for the progress of a society that is in a prosperous condition. This research aims to determine the effect of public sector investment in education and health on the level of welfare in Tulungagung district in 2008-2022. This research is descriptive quantitative, using multiple linear regression analysis. The research results show that the T count for the education level variable (X1) is 6.033 while the T table is 1.782 so that the T count < T table (6.033 > 1.782). So, the level of education has a positive and significant effect on the level of community welfare. T count for the health level variable (X2) is 5.622 while T table is 1.782 so T-count > T-table (5.622 > 1.782). So, the level of health has a positive and significant effect on the level of community welfare and together the variables level of education (X1) and level of health (X2) have an effect on the level of welfare in Tulungagung Regency (Y).